Indonesian Economic Diplomacy through the Consulate General of the Republic of Indonesia - Ratnie Hidayati Oktaviane Masri; Nur Azizah (Budapest International Research and Critics University, 2024)
The net value of Indonesia's exports to Viet Nam in 2022 was USD 8,487,713,800, while Viet Nam's imports to Indonesia amounted to USD 4,394,327,745. In 2022, the tourism sector received a total of 68,076 visitors from Vietnam. In 2022, Indonesian investment in Viet Nam reached a total of USD 638.88 million, spread across 106 projects. The Consulate General of the Republic of Indonesia in Ho Chi Minh City (KJRI HCMC) engages in economic diplomacy to maximize economic advantages for Indonesia. The objective of this study is to examine the economic diplomacy carried out by the KJRI HCMC, which serves as the official representative of the Indonesian government in the areas of trade, tourism, and investment. This study employs the principles of economic diplomacy and national interestThere is no text provided. The research employed a descriptive qualitative research method, utilizing primary data obtained through internships at the KJRI HCMC, as well as secondary data in the form of documents or publications. Data collection is conducted through the utilization of observation, interview, and documentation techniques. The study findings indicate that the KJRI HCMC engages in economic diplomacy primarily in the trade sector. This is achieved through the facilitation of Indonesian delegations and the organization of seminars and business meetings. Within the investment sector, tasks involve facilitating company delegations and conducting working visits. The tourism sector facilitates tourism activities by coordinating the agenda and actively participating in festivals.